Feathered dinosaurs - Sloan, Christopher; Currie, Philip J. (Washington, D.C. : National Geographic Society, 2000)
Looks at the evidence of dinosaurs with skeletal structures and feathers so similar to birds and why that is convincing many scientists that birds evolved from dinosaurs.
Includes index.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
6.8.
6.8
Keywords: Birds, Fossil -- Juvenile literature; Birds -- Origin -- Juvenile literature; Dinosaurs -- Juvenile literature; Birds, Fossil; Birds; Dinosaurs; Birds -- Origin; Dinosaurs; Fossils